Does green investment tax exemption drive Malaysia towards green economy? - Muhammad Jasrim Ku Hakim; Fathin Faizah Said; Nor Ghani Md Nor; Zulkefly Abd Karim; Aisyah Abd Rahman; Syajarul Imna Mohd Amin (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores whether Green Investment Tax Exemption (GITE) policy may effectively guide Malaysia towards a green economy by balancing carbon emission reductions with economic growth. Despite growing empirical studies on tax incentives, integrating GITE with macroeconomic dynamics remains limited in Malaysia. This paper addresses this gap by developing New Keynesian Dynamic Stochastic General Equilibrium (NK-DSGE) model tailored to Malaysia’s green economy scenario under the GITE policy through incorporating households, low-carbon firms, banking sector, government, and central bank. The model simulates the macroeconomic and environmental impact of GITE. Simulation results demonstrate that GITE enhances green investment, reduces loan demand, increases capital accumulation, employment, and GDP, while reducing carbon emissions in the long-term. However, the rise in wages leads to a temporary decline in consumption driven by intertemporal substitution. Policy implications suggest that while GITE is effective in promoting the transition to low-carbon economy, it incurs fiscal costs and limits government revenue and spending capacity. Policymakers are thus encouraged to implement complementary policies to support GITE in order to reduce the reliance on tax incentives and foster public-private partnership. Such integrated policy approach ensures Malaysia stays on track towards achieving its Net-Zero 2050 commitment and long-term sustainability objectives.